Exploring games to enhance arabic Morphology learning - Siti Rohani Jasni; Mohd Hatib Ismail (ResearchGate, 2024)
The difficulty in mastering Arabic morphology is the main obstacle for students in acquiring the four main Arabic language skills: reading, writing, speaking, and listening. However, learning Arabic morphology heavily depends on the strength of memory to memorize the numerous word patterns. Relying solely on memorization techniques can lead to confusion and misinterpretation in understanding the context of sentences. This study aims to discuss aspects of memorization and the integration of games in learning Arabic morphology. This study is a literature review through content analysis and described descriptively. The findings show that previous studies on the use of games in learning have a positive impact on students’ cognitive, behavioural, interest, and motivation aspects. The literature review also found that the integration of games in learning can help reinforce memorization and facilitate students’ understanding. The implications of this study are expected to open opportunities for educators to explore the dimension of games in learning to be adopted in the teaching and learning of Arabic morphology.